EFFECTS OF THE 2-AMINOIMIDAZOLINE ON RAT KIDNEY AND LIVER - Cevik, A.; Karatas, F.; Kara, H.; Genc, M.; Koca, M. (Indian Veterinary Journal, 2008)
The aim of the present study was to investigate the effect of 2-aminoimidazoline (2-Amdz) administration on the levels of antioxidant vitamins A, E, C and Malondialdehyde (MDA) on pathological changes in liver and kidney of rats.
Keywords: Performance Liquid-Chromatography; Malondialdehyde; Benzimidazoles